September 2019 Placement Ads (The Accounting Review, 2019)
FAIRFIELD UNIVERSITY, Accounting Department invites applications for a tenure-track position in the AACSB-accredited, nationally ranked Dolan School for Fall 2020. Preference will be given to candidates who have an ability to teach in multiple areas. Candidates must have or be near completion of a doctoral degree, have professional accounting certification, and a strong commitment to teaching, research, and service. Fairfield University is an independent Jesuit comprehensive university with an active, collegial, pluralistic faculty. Fairfield's Accounting Program was ranked #1 in Connecticut by The Accounting Path. Application Instructions: Upload the following materials: cv; application letter; transcripts; documentation of professional certification; teaching philosophy; syllabi/teaching evaluations, if available; and contact information for three references. Go to: https://www.fairfield.edu/hr/employmentopportunities/facultyopportunities/. Fairfield University is an Equal Opportunity/Affirmative Action Employer, committed to excellence through diversity, and welcomes applications from women, persons of color, veterans, and members of historically underrepresented groups. The University will provide reasonable accommodations to all qualified individuals with a disability.THE UNIVERSITY OF TOLEDO, College of Business and Innovation, Department of Accounting invites applications for two tenure-track positions at the Assistant Professor level (beginning in Fall 2020). A Ph.D. or ABD in Business Administration from an AACSB-accredited program with a specialization in Accounting is required. For ABD applicants a Ph.D. by Fall 2020 is required. Applicants should demonstrate potential for high-quality research and teaching. Candidates with teaching interests/experience in tax or financial are preferred. A professional certificate (e.g., CPA or CMA) is preferred. Applicants must apply at http://jobs.utoledo.edu, in order to be considered for the position. Review of applications will begin August 2019 and will continue until the position is filled. A complete application packet must include: a cover letter, curriculum vitae, statement of research and teaching, a list of three professional references with contact information, and any other supporting documents (e.g., job talk paper, teaching evaluations, etc.). Please submit these materials through the University of Toledo application website. For further information, please contact: Diana Franz, Chair, Department of Accounting, DIANA.FRANZ@utoledo.edu. The University is dedicated to the goal of building a culturally diverse and pluralistic faculty and staff committed to teaching and working in a multicultural environment and strongly encourages applications from women, minorities, individuals with disabilities and covered veterans. The University of Toledo does not discriminate in employment, educational programs, or activities on the basis of race, color, religion, sex, age, ancestry, national origin, sexual orientation, gender identity and expression, military or veteran status, disability, familial status, or political affiliation. The University of Toledo is an Affirmative Action/Equal Opportunity Employer.UNIVERSITY OF DAYTON, Department of Accounting invites applications for a tenure-track position at the Assistant or Associate Professor level beginning August 16, 2020. Qualified candidates must possess the demonstrated ability to teach upper-level undergraduate or master's courses in financial or managerial accounting. Candidates must meet and have the potential to maintain AACSB business and accounting accreditation requirements for “Scholarly Academic” (SA) status, be at least ABD (completed all course and comprehensive exam requirements for a Ph.D.) in accounting at an AACSB- or EQUIS-accredited institution, have a successfully defended dissertation proposal, have a relevant professional certification (e.g., CPA, CMA) or two years of relevant professional experience in their area of specialty, and have effective writing skills. To qualify as Associate, candidates must meet all previously specified requirements, hold a Ph.D. in accounting from an AACSB- or EQUIS-accredited institution, and have a demonstrated successful record of research, teaching, and service. Preference will be given to candidates who hold a Ph.D. in accounting from an AACSB- and/or EQUIS-accredited institution, have demonstrated progress toward successful scholarly publications, have successful university teaching experience, have both relevant professional certification (e.g., CPA, CMA) and relevant professional experience in their area of specialty, have experience mentoring students and/or staff from diverse backgrounds, have effective interpersonal skills, an ability to work collaboratively, and effective, demonstrated verbal skills. Apply by completing the application at: http://employment.udayton.edu/cw/en-us/job/497301/assistant-or-associate-professorLOYOLA MARYMOUNT UNIVERSITY, Department of Accounting invites applicants for a tenure-track position at the Assistant or Associate level, effective Fall 2020. The Department of Accounting offers a B.S. and M.S. in Accounting. Candidates must have earned a doctorate in Accounting from an AACSB-accredited university by August 2020. All candidates should demonstrate a strong commitment to scholarly research and excellence in teaching. Candidates whose research and teaching interests are in the tax area will receive priority. Candidates with research and teaching interests in other areas of accounting will be considered. Relevant professional experience and professional certification (CPA or CMA) are desirable. Salary is competitive. To apply for this position, please submit a letter of interest and current curriculum vitae. Please be prepared to submit three letters of recommendation and student evaluation summaries upon request. Applicants should apply online at: http://jobs.lmu.edu/hr/postings/40041/. Loyola Marymount University, a Carnegie classified R2 institution in the mainstream of American Catholic higher education, seeks qualified applicants who value its mission and share its commitment to inclusive excellence, the education of the whole person, and the building of a just society. Women, persons of color, LGBTQ and gender-nonconforming individuals, people living with disabilities, and others with diverse life experiences and beliefs are encouraged to apply. Visit https://www.lmu.edu/ for more information. LMU is an Equal Opportunity Employer.RUTGERS, THE STATE UNIVERSITY OF NEW JERSEY, Rutgers Business School–Newark and New Brunswick, Accounting and Information Systems Department is seeking a full-time tenure-track faculty member at the rank of Assistant/Associate Professor. Responsibilities: Candidates must be dedicated to providing quality instruction and undertaking independent scholarly activity appropriate for advancement within Rutgers University. Responsibilities also include Department and University service. Job Qualifications: A strong background and research expertise in any accounting area are required. The candidate should be capable of conducting high-quality, innovative research, and teaching in his/her chosen area of accounting. A Ph.D. degree from an AACSB-accredited school in the field of accounting or a related discipline is required. A strong preference will be given to seasoned candidates with an outstanding research record and with interest in working with doctoral students. Teaching load and salary are competitive with research universities. Application Procedure: Please submit your application (cover letter, three names of your letter writers, research paper[s], and cv) electronically at: http://jobs.rutgers.edu/postings/94023/. About Rutgers: The Accounting and Information Systems Department has 40 full-time faculty members. The Rutgers Business School offers B.S., M.B.A., Master's of Accountancy, and a Ph.D. program with two concentrations, one in accounting and one in accounting and information systems. All qualified applicants will receive consideration for employment without regard to race, religion, sex, sexual orientation, gender identity or expression, national origin, disability, protected veteran status, or any other classification protected by law. Women and minorities are especially encouraged to apply. Diversity and inclusion are a key element of Rutgers University's Strategic Plan. In the goal to enhance faculty diversity, Rutgers defines diversity very broadly. Diversity may include, but is not limited to gender, ethnicity, race, culture, national origin, or other personal or professional characteristics are or underrepresented in the or of For information please the at the following For to: OF Accounting Department invites applications for a tenure-track Assistant or Associate Professor position beginning as as 2020. include teaching undergraduate and and maintain an program of research to and providing to the and or educational requirements include an earned doctorate in Accounting, a with an in for applicants to teach or an earned doctorate in business with accounting experience or in accounting. Candidates completion of an earned doctorate will also be considered. A CPA certification or a to is preferred. the following application materials at letter of curriculum vitae, of teaching courses are in teaching and/or and and the contact information for three references. to Accounting is an UNIVERSITY invites applications for two tenure-track positions Fall 2020 at the rank of Assistant or Associate Professor. tax and managerial are of candidates from all areas of accounting will research and teaching A Ph.D. in accounting is ABD candidates will be considered. Candidates should possess a strong to research at the with an background strongly an ability to an program of A of teaching potential and commitment to their are also Please apply at and provide the following for cover letter, current and personal statement of For the position, please contact: Department Chair, Accounting Business For the application please contact UNIVERSITY, College of Business is seeking applicants for a tenure-track faculty position in Accounting, beginning in August 2020. and Responsibilities: The position will include teaching a of courses in accounting at the undergraduate and include program and The College of Business is AACSB-accredited, and professional is Qualifications: earned Ph.D. in accounting from an university or a related Ph.D. as business with accounting near Ph.D. completion will be considered with a of degree completion within one of Applicants are to be qualified to AACSB and Candidates must have the ability to and meet the of the position in a and student In candidates should have and interpersonal and skills. To apply for this position, please STATE UNIVERSITY, Department of has two tenure-track faculty positions at the Assistant Professor teaching for the two positions are in and Accounting Information include a commitment to high-quality teaching at both the undergraduate and level, courses in of in programs, to and publications, and University and service. The for these positions is August 2020. applicants should the complete job with all requirements and apply online at: UNIVERSITY, School of Department of Accounting invites applications for a full-time or tenure-track faculty Associate or 2019 to teach at both the New University School of Business in and New The successful will be to teach both and courses at the undergraduate and level, will be to and course for the accounting and maintain scholarly in their Candidates should have an earned doctorate in Accounting or a related or provide will be within one of the In very as by the University, the of a doctorate or degree may not be For job and to NEW UNIVERSITY, College of Business invites applications for a tenure-track accounting faculty position at the Assistant or Associate Professor level to begin in Fall 2020. Candidates are to hold a Ph.D. degree in Accounting or related discipline from an AACSB-accredited College of The include research, teaching, and activities to the University, the the and the for and New University is a institution more full-time undergraduate students. and professional are through of and and and School of Apply at candidates whose background may to the further of New University is an Equal Opportunity seeks to two tenure-track positions in Accounting, at the rank of Assistant or Associate on educational and experience at the of include: undergraduate and/or Accounting courses as Accounting, Accounting, Accounting Information Systems and Accounting and in and strong and research and in Accounting or related meet or the requirements for faculty or in professional or activities in or in an to a and the and of the College and in student of as as at all of the reasonable as Qualifications: Ph.D. ABD with Ph.D. completion of 2019 or in Accounting or a related field from a institution Apply at: UNIVERSITY, School of Business invites applications for a tenure-track position in Business Teaching for this position will be the business course in the undergraduate business program and courses in financial professional and in the of program will begin in Fall 2020. The successful candidate will be committed to effective and teaching, will a program of scholarly activity the potential to the of and will with the business Preference will be given to candidates who have an or Master's in professional or work experience in tax or financial For a complete of the position, please or contact University, an Employer, is committed to and UNIVERSITY, Department of Accounting invites applications for a tenure-track Assistant Professor or a position in Accounting, effective August 2020. Applicants must be committed to and demonstrate the potential for excellence in and Applicants from all areas of accounting will be considered. preference will be given to candidates with experience and in accounting and/or and professional The teaching load for the position is for tenure-track Assistant Professor and for A Ph.D. in Accounting or a related field is for as Assistant Professor. For a degree in accounting or and experience in accounting or is required. For a complete of the position, please or contact University, an Employer, is committed to and OF College of Business invites applications for a tenure-track Assistant Professor in Accounting. will begin in August 2020. Candidates will be to teach courses within the field of Accounting a at both the undergraduate and in Accounting Information Accounting Accounting, and/or Candidates are to have a commitment toward teaching, research, and service. earned doctorate degree by a or institution in the field specified in the position in Accounting or ABD from AACSB or school of business will be given priority. should have to research in one of the accounting Relevant experience in teaching area strongly preferred. Accounting certification CPA preferred. teaching experience in higher education environment at the level of Teaching Assistant or higher is required. must provide of teaching and experience preferred. must be qualified Go to: STATE UNIVERSITY, College of Department of Accounting invites applications for one or more tenure-track faculty positions in Accounting. The position August and include teaching, research, and service. A doctorate in accounting from an AACSB-accredited school strong of completion for individuals for a position at the Assistant is required. with teaching interests in all areas of accounting with individuals expertise and/or interest in more one area preferred. Candidates must demonstrate the ability to in accounting and have a to an working with doctoral students. The following documents are letter of curriculum vitae, an of scholarly work to be to faculty and Ph.D. and three letters of Candidates must materials online at: to be considered for the position. will also be to submit a of teaching Review of applications will begin and will continue until position is filled. should be to: Chair, and UNIVERSITY, College of Business invites applications and for a tenure-track position beginning in Fall 2020 or if Qualified candidates will have an earned doctorate in Accounting with a teaching and scholarly in financial accounting. and relevant professional experience is Candidates should have a research, teaching, and record at the Associate Professor or Professor Teaching load is courses and is The College seeks a with a commitment to teaching as as include to and The Department to the accounting in the financial accounting as as mentoring for and to the University, and the business and University is a Catholic university in with a in and encourages applications from qualified individuals of all who to the educational of the has ranked by as one of the in the The College of Business is by the AACSB with undergraduate and of students. has in the The College a program in the Fall The Department of Accounting is by the AACSB and has ranked in the undergraduate accounting by The Department has tenure-track with two and three full-time The Department a of Accounting degree has the the CPA have at the of the in and in the in on a national To be candidates should submit a letter of and other relevant supporting through the following may be to: CPA, Chair, Department of Accounting, College of University, UNIVERSITY, College of Business Department of Accounting invites applications for a at the Associate or Professor level to begin 2020 faculty at the and also at the university in and are related to faculty activities and students and and and The with the to and the mission and and on the A doctorate in Accounting or related field from an AACSB-accredited institution and a record of effective teaching, scholarly and appropriate for at is required. For information and to is by and is an Employer.UNIVERSITY OF Department of invites applications for an of in and Accounting. have for undergraduate accounting courses at the and Qualifications: CPA, M.B.A., or degree in or a field relevant to course at the of work experience in a business and teaching experience demonstrated by teaching, experience, research or professional Application must be through the online Please to in all and application requirements may be at: The University of is an Equal Opportunity/Affirmative Action seeks applicants for an Assistant/Associate Professor to a tenure-track position in a full-time The successful candidate will provide instruction at the undergraduate and and course and/or undergraduate and curriculum for and/or undergraduate and/or instruction both online and/or on any of the university or experience teaching online or in a teach the and/or in the in scholarly activities to in work with others in the University, and to the University, and and to the of a work environment encourages and ability to with of other or Ph.D. or in Accounting from an AACSB-accredited institution or Ph.D. or in a related discipline from an AACSB-accredited program include a of in level Candidates are ABD will be considered. Go to: UNIVERSITY, College of Department of invites applications for a tenure-track position in accounting information at the Assistant or Associate rank in Fall 2020. Candidates should be to teaching and for be to and as the and to the of and the The candidate will be to the position of of the for Accounting and and be for the of the and for students certification is and of the certification is preferred. Teaching experience at the university level is and a on student and student is UNIVERSITY, Accounting Department seeks applicants for one full-time position August 2020 to teach undergraduate and courses and will be on Preference will be given to candidates teaching courses in accounting or Qualifications: or ABD in Accounting, or related Job University teaching, research, and service. Candidates must have a commitment to research in business to quality and in teaching and Please your to to your Applicants will submit application materials online the position is is an Equal Opportunity/Affirmative Action and encourages applications from and minorities as as other qualified OF College of Business and Department of Accounting seeks a tenure-track Assistant Professor beginning August to is a full-time position with for teaching undergraduate and courses in conducting research, and providing to the university and The successful candidate will be to teach a of accounting courses as of the undergraduate accounting program and the Master's of The candidate will also be to an research in and to the the and society. Ph.D. in Accounting or related or from an AACSB-accredited institution is required. ABD candidates may apply. To apply this The Job is OF THE School of in Business an innovative and who has the skills, and experience to and the accounting programs, the accounting research and its with The School offers a of in Accounting, a of Accounting, and a program the two The successful candidate will teach undergraduate and accounting scholarly the accounting and maintain and with accounting and of and accounting may be at the Associate or Professor level on is August 2020. Applicants must hold at least an Associate position, with at their current Teaching expertise in any area of accounting will be considered. Preference will be given to with experience in The successful candidate will hold a doctorate in accounting from an AACSB-accredited school and provide of an research Go to: UNIVERSITY, Department of Accounting seeks applications for a full-time tenure-track position in accounting in the rank of Assistant Professor or Associate to in the or Fall 2020. is an AACSB-accredited university on New is for with and innovative to and The position teaching undergraduate and and in service. The successful must be and maintain Responsibilities: members teach teach level undergraduate courses in Accounting, or and courses in Accounting or Teaching at any of the University's in at and on Qualifications: a degree in accounting or in business with at least in accounting from an AACSB-accredited and CPA with at least reasonable experience working for a CPA should include a letter of curriculum vitae, of teaching from the three and CPA of are as of the To be applications must be through the UNIVERSITY, School of Accounting Department invites applications for a tenure-track rank faculty position as an Associate, or Professor to August 2020. Responsibilities include conducting quality research and high-quality teaching at both the and undergraduate All areas of teaching will be considered. earned doctorate in accounting from an AACSB-accredited business school is required. to completion will be but the degree will to be to and salary upon The Department is by AACSB and students with and 40 students with of is a university with students is for national and a of and The University is from the and your to Professor OF College of Business is seeking a qualified accounting for a tenure-track position at the Assistant/Associate Professor of Accounting level to August 2020. Applicants with teaching and research in and/or information are but applicants with other are also encouraged to apply. Applicants must have a Ph.D. or in accounting or a Master's in from an AACSB-accredited teaching experience and professional certification will be preferred. Applicants who are ABD will be considered if will be completing their degree by August 2020. Applicants should submit a cover letter, current curriculum with three a teaching a of teaching evaluations, and student with the position of applications for the position will be begin 2019 and applications will be considered until the position is filled. applications be to position Please contact Chair, if have any the position. is an Affirmative Equal Opportunity and is committed to diversity in its student and OF College of Business is seeking and qualified accounting applicants for an Accounting August 2020. Applicants with professional and/or teaching experience in accounting information or are but applicants with other are also encouraged to apply. Applicants for the position must have a Master's degree, experience in accounting of or a and be as a scholarly with an research will be preferred. position is on Applicants should submit a cover letter, current curriculum with three a teaching a of teaching with the position for the position will be considered until the position is filled. applications be to: Please contact Chair, if have any in to the position. is an Affirmative Action/Equal Opportunity and is committed to diversity in its student and UNIVERSITY, School of Assistant Professor of Accounting, position is upon a background Applicants must have a Ph.D. by August and have research and teaching in or tax accounting. Candidates should be qualified to teach undergraduate or Applicants are to curriculum vitae, three letters of and of teaching at: by 2020. will not discriminate in any program or activity on the basis of race, color, religion, national origin, sex, age, disability, information, veteran status, sexual orientation, or gender identity and The for and is to and may be at the Administration UNIVERSITY invites applications for a Assistant Professor of Accounting position Fall 2020. candidates from all areas of but are in candidates who have experience in or and a Ph.D. or a Master's degree with three years of The of faculty is to the teaching mission of the Department and to provide to faculty members must in activities and Department activities with their on the of their educational and professional experience as as for individuals should apply at: and provide a cover letter, current and a personal statement of For the position, please contact Department Chair, Accounting Business For the application please contact UNIVERSITY, School of of invites applications for tenure-track of Accounting and will until filled. applicants for Assistant Professor should a doctorate degree in the of financial and or tax from a or at least of the ability to in a strong commitment to excellence in research and teaching. applicants for Professor should a record of are and teaching potential or to be an who is capable of undertaking national key research or a strong faculty for the and teaching and competitive research as as other Applicants should submit all materials to of STATE College of Department of Accounting invites applications for one or more full-time accounting faculty begin August and include teaching, research, and service. earned doctorate in accounting or related field from an AACSB-accredited school by the is required. Teaching will include to and/or Accounting as as other to be on The teaching load will be a research The successful candidate is also to provide to the University, or with The following documents are letter of curriculum vitae, an of scholarly and the of three references. letters will be for candidates considered for will also be to submit a of teaching Candidates must materials online at is Review of applications will begin and will continue until the position is filled. should be to the and UNIVERSITY OF NEW invites applications for an accounting position for August 2020. Preference will be for who have teaching interests in of or accounting. Candidates must have the Ph.D. with an accounting verbal and are Salary is and competitive. The Department offers the undergraduate accounting degree and two Master's in Accounting and M.S. in with students. The Department has AACSB accounting accreditation at both the and undergraduate Candidates should a to: Professor Department of Accounting, College of Business University of New New Women, minorities, and persons with disabilities are encouraged to apply. The University of New is an Affirmative Action/Equal Opportunity UNIVERSITY OF College of Department of Accounting invites applications for a tenure-track position as an Assistant/Associate Professor of Accounting for the applicants with an earned doctorate degree in Accounting from an AACSB-accredited or accounting Candidates should demonstrate excellence in teaching and a commitment to scholarly Teaching interest in the area of and accounting is and expertise in accounting experience, and professional certification are desirable. Review of applications will begin For further and to please at: The University of is an Affirmative Action/Equal Opportunity UNIVERSITY, College of Business and Administration School of Accounting, invites applications for an Assistant/Associate Professor of Accounting for Fall 2020 to teach courses in accounting at the undergraduate and in accounting or accounting information preferred. teaching load is A doctorate in Accounting is preferred. ABD candidates to completion will be considered. Salary is competitive with AACSB University is a comprehensive university dedicated to quality teaching. is in with a is and limited to students in the and of the University. The is by cover letter, current and a list of three references to: Chair, School of Accounting, University, University University is an Equal Opportunity